The Effect Of Annealing On Random Lasing In Zinc Oxide Nanorods Grown By Chemical Bath Deposition - Maad Tazri, Nur 'Izazi (2019)
One dimensional ZnO nanostructure have been extensively studied due to its potential application in electronic and optoelectronic devices. The work presented here utilizes ZnO nanorods prepared by CBO method on pretreated glass substrate.